Anne's House of Dreams : Anne of Green Gables #5 - Montgomery, L. M. 1874-1942 (Lucy Maud) (New York : Bantam Books, 1992)
Anne and Gilbert settle into their first home and Gilbert takes on his uncle's medical practice in Four Winds Harbor. New friends and neighbors enrich their lives: Captain Jim, the lighthouse keeper, outspoken but kindly Miss Cornelia Bryant, and the sad, lovely Leslie Moore. And the Blythe family is enlarged!
Keywords: Prince Edward Island (Canada) -- Fiction; Marriage -- Fiction; Friendship -- Fiction